Value-addition in food products and processing through enzyme technology (Elsevier Academic Press, 2021)
Value Addition in Food Products and Processing using Enzyme Technology offers an updated review regarding the potential impact of new enzymes and enzyme technology on the food sector. The book brings together novel sources and technologies regarding enzymes in value added food development, food production, food processing, food preservation, food engineering and food biotechnology. It will be extremely useful for different types of readers, including food scientists, academic and food biotechnologists, but will also be ideal for students studying food-related courses. This book includes concise and up-to-date research information from multiple independent scientific papers from around the world. This is a essential, multidisciplinary text for research and development professionals, research scientists, and academics in food, biotechnology, and agriculture industries. It addresses safety issues and includes the sources, screening, immobilization and application of food-grade enzymes in food.
Keywords: Food industry and trade -- Technological innovations.; Enzymes -- Industrial applications.; elektronické knihy; electronic books